The Asymmetric Impact of War: Resilience, Vulnerability and Implications for EU Policy - Giuseppe Celi; Dario Guarascio; Jelena Reljic; Annamaria Simonazzi; Francesco Zezza (Intereconomics, 2022)
In 2019, over 96% of EU27 oil needs, nearly 90% of natural gas and over 43% of solid fuels were met by net imports, with the largest share coming from Russia (35% of oil, 40% of natural gas and 20% of solid fuels consumed in EU27). The decline in the share of oil since 2016 was more than off-set by the increase in gas and solid fuels.
Keywords: F51; O52; 330